Force-velocity-power variables derived from isometric and dynamic testing: metrics reliability and the relationship with jump performance - Vieira, Amilton; Cunha, Rafael; Gonçalves, Carlos; Dal Pupo, Juliano; Tufano, James (PeerJ, 2024)
We investigated the convergent validity and intrasession reliability of force, velocity, and power (FVP) variables and the dynamic strength index (DSI) obtained from isometric midthigh pull (IMTP) and squat jump (SJ) testing. Fifteen male combat sports athletes (27 ± 5 years, 77 ± 9 kg, 1.76 ± 0.1 m, 14 ± 6% body fat) participated in a 2-days study. The first day involved testing familiarization, while the second was dedicated to IMTP and SJ testing. Maximal isometric force (Fiso ) was obtained from IMTP, while mean force, mean velocity, jump height, and jump impulse (J) were gathered from SJ. To analyze the FVP, we calculated the linear relationship between force and velocity, which allowed us to obtain the slope of the relationship (SFV ), the theoretical velocity at zero force (V0 ), and the theoretical maximal power (Pmax ). DSI was obtained as a ratio from SJ peak force and Fiso . The convergent validity was investigated using Spearman's ρ coefficients to assess the relationships between jump height and J with Fiso , V0 , SFV , Pmax , and DSI. The intrasession reliability was assessed using intraclass correlation coefficients (ICC) and coefficient of variations (CV). All variables demonstrated acceptable reliability scores. ICC ranged from moderate to excellent, and the mean CV was <10%. We found a "very large" correlation between jump J and Pmax , while jump height was not correlated with any variable. In conclusion, the IMTP and SJ combination is a practical way to determine FVP producing capacities that can be reliably measured (intrasession). The Pmax , derived from FVP, was correlated with jump performance, which might evidence the convergent validity of the method.
Keywords: Humans; Isometric midthigh pull; Assessment; dospělí; Dynamic strength index; Performance; Squat jump; lidé; Thigh; reprodukovatelnost výsledků; Two-point method; Adult; pohyb; Male; Reproducibility of Results; Movement; Exercise; Linear regression; biomechanika; stehno; mužské pohlaví; cvičení; Biomechanical Phenomena